PERBEDAAN PENYIMPANGAN PENGELOLAAN KEUANGAN NEGARA SEBELUM DAN SESUDAH DILAKUKANNYA PENILAIAN INISIATIF ANTI KORUPSI PADA KEMENTERIAN XYZ - Tri Rahayu Kusumaningtyas; Susi Dwimulyani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
This study was conducted to compare and obtain empirical evidence of differences in state financial management irregularities before and after the assessment of anti-corruption initiative of the Ministry of XYZ in 2005 - 2014. The hypothesis was tested that irregularities in the financial management of the state prior to the assessment of anti-corruption initiatives differ significantly than after the assessment of anti-corruption initiatives.Design research is comparative quantitative research, the variable is assessment of anti-corruption initiatives and irregularities in the management of state finances. The sample in this study using nine of the 10 Echelon Unit in the Ministry XYZ conducted an audit by the Inspectorate General of the Ministry of XYZ from 2005 through 2014. Statistical tests performed using Wilcoxon Signed-Ranks Test with significance level used was 0.05.Results of Wilcoxon Signed-Ranks Test can be delivered as follows: 1) the average value of the state's financial findings before assessment of anti-corruption initiatives greater than after assessment of anti-corruption initiatives; 2) the difference between the findings of state finances after assessment of anti-corruption initiatives and before assessment of anti-corruption initiatives negative value, means the value of the state's financial findings after doing assessment of anti-corruption initiatives smaller than before assessment of anti-corruption initiatives; and 3) irregularities in financial management of state prior to assessment of anti-corruption initiatives significantly different than after assessment of anti-corruption initiatives.